Women, periodicals, and print culture in Britain, 1830s-1900s : the Victorian period - Easley, Alexis, 1963-; Gill, Clare; Rodgers, Beth (Edinburgh history of women's periodical culture in Britain., 2019)
The period covered in this volume witnessed the proliferation of print culture and the greater availability of periodicals for an increasingly diverse audience of women readers. This was also a significant period in women's history, in which the 'Woman Question' dominated public debate, and writers and commentators from a range of perspectives engaged with ideas and ideals about womanhood ranging from the 'Angel in the House' to the New Woman. Essays in this collection gather together expertise from leading scholars as well as emerging new voices in order to produce sustained analysis of underexplored periodicals and authors and to reveal in new ways the dynamic and integral relationship between women's history and print culture in Victorian society.